Revolusi Digital Arsitektur Multimedia Sebagai Fondasi Ruang Pembelajaran TIK - Suci Ramadhani Herman; Andy Satria; Willy Aldo Doglas Hutabarat; Salsabila Thalia (JURNAL PENELITIAN SISTEM INFORMASI (JPSI), 2024)
This research explores the implications of the digital revolution on multimedia architecture as a fundamental foundation in the design of information and communication technology (ICT) learning spaces. Through a thoughtful approach to the integration of digital technologies into the concept of multimedia architecture, this research aims to determine the significant impact in innovating learning experiences and improving the effectiveness of IT learning. An in-depth analysis of the relationship between architectural elements and digital technologies provides a better understanding of the strategic role of multimedia architecture as a driver for the development of study spaces. By detailing how integrating digital technologies into multimedia architectural elements can shape cutting-edge learning experiences and improve the effectiveness of ICT learning, this research creates an in-depth understanding of the complexity of the relationship between physical space and the development of digital technologies. A comprehensive analysis of the aesthetic, functional and technological aspects of multimedia architecture provides insight into its important role in shaping a paradigm shift in environmental studies. The results of this research make an important contribution to the design of learning spaces that not only meet the development of modern technology but can also meet the complexity of learning needs in the digital era. . Design learning spaces that are adaptable and meet the demands of modern technological developments.